Nephrotic syndrome in Pediatrics: regarding two clinical cases - Villacís, Doménica (Revista Gregoriana de Ciencias de la Salud, 2024)
Pediatric nephrotic syndrome is a common entity in children and is characterized by proteinuria, hypoalbuminemia, and edema. Minimal change disease (MCD) is the most common histological form. The objective of this work was to analyze two cases of children with classic symptoms of nephrotic syndrome, managed with steroid treatment and follow-up by Pediatric Nephrology. Most patients respond well to treatment, but some may relapse or be corticosteroid-resistant, which can lead to kidney failure. Nephrotic syndrome is the most common primary glomerulopathy in pediatrics and requires appropriate diagnosis and management to avoid short- and long-term complications. Despite corresponding to a relatively common disease in Pediatrics, its diagnosis is usually delayed, requiring the intervention of different physicians until finally reaching the corresponding diagnosis and treatment, hence the importance of the review and presentation of clinical cases.